Indigenous knowledge and economic resistance: Local strategies against market penetration in Eastern Indonesia - Az-Zahra, Andi Nurfatimah; Guntur, Ahmad Ismail (Edelweiss Applied Science and Technology, 2025)
This research examines how local wisdom is utilized as a form of resistance to the dominance of market economic expansion within indigenous communities in Eastern Indonesia. Employing a qualitative approach based on case studies, the study explores the roles of traditional ecological knowledge, ritual abstinence practices, and communal land ownership systems in confronting the process of natural resource commodification while preserving the sustainability of local cultures. Data were collected through in-depth interviews, participatory observation, and document review across several purposively selected indigenous communities. The findings indicate that these elements of local wisdom not only hold symbolic significance but also serve as practical strategies for maintaining community sovereignty and ecosystem integrity. This study contributes significantly to discussions on cultural sustainability, the recognition of indigenous peoples’ rights, and critiques of the neoliberal development paradigm, which emphasizes market-oriented growth.